A South African Convivio with Dante Born Frees' Interpretations of the Commedia - Fanucchi, Sonia; Virga, Anita (Studi e saggi, 2021)
This book offers a collection of South African university students' written responses to the Commedia and scholars' commentary on them. The students' collection includes writings of all genres and subjects: prose, poetry, personal reflection, dialogue, non-fiction based on the first two cantiche of the Commedia. Some are autobiographical and others are fictional stories, but they all have in common a very personal (and South African) approach to Dante's text. The scholarly essays of the second part are concerned with the unusual way in which Dante is appreciated by our youth: not as a remote figure only encountered in the hallways of the literature department, but as an intimate presence, a guide, a friend whose language is familiar and invites a response.